HUKUM MENJATUHKAN THALAQ MELALUI TULISAN MENURUT PENDAPAT IBN HAZM - Geubrina Razeki (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2019)
Basically, thalaq is the husband's right. This means, only the husband has the right to drop thalaq. The fall of thalaq can occur if the husband says lafaz thalaq to his wife both clearly and vaguely (kinayah). But the problem that arises is if the husband does not drop thalaq orally or pronounced, but through writing, then the wife reads it. The law dropped thalaq through writing according to the four schools of law is falling thalaq if the husband intends it. But in this case Ibn Hazm who is a prominent Islamic figure argues that thalaq dropped by writing is not considered to fall thalaq. Legal dropped thalaq through writing according to Ibn Hazm is not considered falling thalaq because according to Ibn Hazm dropping thalaq through writing is an act that is not based on any source of law, especially al-Qur'an and Hadith, because there is no word of Allah or the Hadith of the Apostle clearly and expressly mention about the law of dropping thalaq through writing. Ibn Hazm based his opinion on the Qur'an al-Baqarah verse 229. The legal line contained in the al-Baqarah letter is about thalaq, namely thalaq in general. And there is no specific explanation about the procedure of dropping thalaq, especially there is no dhahir nash which states that dropping thalaq can be done through writing. And in the Koran and in the Hadith also it is not clear about other possibilities referred to from the end of the verse in addition to the common way taken, namely by reciting thalaq. And the verse says that if a husband wants to divorce his wife, let it be in a good way. By Ibn Hazm, who is dhahir nash istinbath, that a good way to reward a wife is to recite it directly in front of his wife, not menthalaq in other ways such as through writing.